Requirements definition model of an information system in a health organization of the city in Mar del Plata, Argentina - Tabone, Luciana Belén (2022)
This study defines the development requirements of an information system in a health organization in Mar del Plata, Argentina. It combines the participatory methodologies of Soft System Methodology and Analytic Hierarchy Process to facilitate organizational decision making. The proposal contributes to the effective and systemic development of the decision-making process, considering the informational infrastructure, characteristics of decision-makers and structural and functional conditions of the organization.